AKIBAT HUKUM PERKAWINAN CAMPURAN TERHADAP HARTA PERKAWINAN (PENETAPAN PENGADILAN NEGERI DENPASAR No: 536/Pdt.P/2015/PN.Dps.) - Widanarti, Herni (Diponegoro Private Law Review, 2018)
In addition to the Marriage Act loaded matters relating to marriage, also regulates marital property. This field is one of the legal field of civil law which has a sensitive nature and potential conflict, therefore setting the field is not as easy as setting the areas of law that are neutral. The complexity of the issues in the field of wealth as a result of a mixed marriage other than by the Marriage Act 1 of 1974 is also dealing with the principles of International Law. The research objective to be achieved is: To know and understand the legal consequences of intermarriage to assets marriages under the Marriage Act 1 of 1974 and to determine the legal consequences of intermarriage against marital property according to the Principles of International Law. The method used in this research is normative juridical approach. The results of the study, due to mixed marriages to property law marriages under the Marriage Act 1 of 1974 concerning marriage, if the parties have not entered into a marriage mate then the property becomes joint property. In its development, the practice of mating agreement can be made after the marriage takes place by submitting an application to the court and has received the court ruling which has binding legal force. With the Denpasar District Court Decision No. 563 / Pdt.P / 2015 / PN.Dps.  Keywords: Marriage, Mixed Marriage, Marriage Treasure